Sheep cooked hams with the inclusion of gellan gum as a substitute for carrageenan - SILVA, Gabriela Pereira; ALTEMIO, Ângela Dulce Cavenaghi; SILVA, Maria Ildilene da; VARGAS JUNIOR, Fernando Miranda de; GOES, Elenice Souza dos Reis (Food Science and Technology, 2025)
This study aimed to develop and characterize Pantanal sheep cooked hams using gellan gum. Hams were prepared with gellan gum (0.0, 0.3, and 0.5%) as a substitute for carrageenan. In terms of centesimal composition, the moisture, protein, and ash contents were not affected by gellan gum, but cooked hams with 0.5% inclusion had lower lipid, carbohydrate, and caloric value contents. The parameters of water activity, pH, yellow intensity, hue, shear force, gumminess, and resilience were not different among the cooked hams. However, the water holding capacity was lower in cooked hams with 0.3% gellan gum, leading to greater luminosity, lower red intensity and saturation, and lower hardness compared to the others. Elasticity was higher in the cooked hams with 0.5% gellan gum, which also showed greater chewiness. The different cooked hams were suitable for consumption due to the microbiological results and the same sensory acceptance, with medians of 7 (moderately liked) for color, taste, texture, and overall acceptance. It can be concluded that the inclusion of 0.5% gellan gum reduces the lipid content and calorific value of cooked hams, increasing the elasticity and chewiness of the product, without affecting its sensory profile.